Professional development of teacher educators: what do they do? Findings from an explorative international study. Issue 2 (15th March 2017) - Van der Klink, Marcel; Kools, Quinta; Avissar, Gilada; White, Simone; Sakata, Tetsuhito
Abstract : The attention being devoted to teacher educators as professionals and their professional development is unquestionably increasing. Whilst much of that attention is being directed at teacher educators in different countries, international comparisons have been quite rare to date. The research question addressed in this study was: 'Do experienced teacher educators from different countries differ in their concerns, professional development activities and developmental goals?' Interviews were conducted with 25 participants from 10 different countries, all of whom were experienced teacher educators. Teacher educators' concerns varied in the course of their careers. During their induction their primary focus tended to be on survival, whereas later on in their careers their concerns became linked to their own professional identity and their students as individuals. Participants from all the participating countries were involved in a range of developmental activities. A large majority was involved in research-related activities which they perceived as an important tool in their professional development. All the participants had plans for their further professional development but sometimes foresaw hindrances to the realisation of those plans, such as a lack of resources and time. The interview data did not provide evidence to suggest clear country-specific differences. In fact, the opposite would appear to be the case: teacher educators from different countries seem to have similar concerns, and their current professional development activities and plans for future development are also quite comparable.